DYNAMIC MECHANICAL PROPERTIES OF CROSSLINKED NATURAL RUBBER COMPOSITES REINFORCED WITH CELLULOSIC NANOPARTICLES (Nigerian Journal of Technology, 2018)
The dynamic mechanical analysis (DMA) of crosslinked natural rubber nanocomposites reinforced with cellulosic nanoparticles obtained from lignocelluloses biomass (coconut husk, bamboo culm and cotton linters) has been investigated and compared with carbon black filled natural rubber vulcanizate. The crosslinked natural rubber matrix based composites were produced by melt intercalation process using two roll mixing mill and vulcanized in a thermally regulated hydraulic press. DMA were carried out in order to obtain their viscoelastic thermo-mechanical spectrum. Results showed decrease in storage modulus (E’) with increasing temperature while glass transition temperatures (Tg) obtained from temperature dependence loss tangent curves were -35.84, 37.30, -34.61, -35.27 and -34.29  oC for neat- natural rubber (NR),  natural rubber reinforced carbon black (NR-CB), natural rubber reinforced bamboo cellulosic particles (NR-BNC), natural rubber reinforced coconut husk cellulosic particles (NR-CHNC) and natural rubber reinforced cotton linter particles (NR-CLNC) respectively. The composite of NR-CHNC was also found to give a higher damping factor of 1.563 compared to NR-CB which gave a value of 1.518. nanocomposites reinforced with cellulosic nanoparticles can provide adequate synergy for loading bearing and vibration isolation application.http://dx.doi.org/10.4314/njt.v37i3.16